Children's consent and paediatric research: is it appropriate for healthy children to be the decision-makers in clinical research?. Issue 5 (18th December 2007) - John, T; Hope, T; Savulescu, J; Stein, A; Pollard, A J
Abstract : Aim: To determine the appropriateness of asking healthy children to make a decision regarding participation in a research study. Methods: Participants constituted a group of children taking part in a follow-up to a vaccine study which involved a blood test to look at the persistence of antibodies. Information about the study was given to each child and following venepuncture an oral questionnaire was completed to establish understanding of the vaccine study. Parental views concerning their child's ability to make a decision regarding research participation were also sought. Results: 73 children participated overall. Following venepuncture 59% (n = 43) had grasped some aspect of the reasoning behind venepuncture with 33% (n = 24) unclear. The majority of parents (n = 55) and a substantial number of children (n = 28) believed that the parent should make the decision about study participation, although it is clear that a significant minority of parents thought it is right to involve the child in that process. Conclusion: New guidance about the requirements for informed consent involving children in research is needed, which can respect the autonomy of the child and the role of the parent, while recognising the limited capacity of some children to understand age-appropriate information.